THE BEGINNINGS OF WORK AND THE RESTORATION OF THE INSTITUTE OF MEDICAL PHYSIOLOGY OF THE FACULTY OF MEDICINE UNIVERSITY OF BELGRADE THROUGH WORK AND CHARACTER OF THE RESTORER PROFESSSOR MILUTIN NEŠKOVIĆ - Djuric, Dragan (Medical Research, 2023)
ABSTRACT With the passage of time and the lack of quality archival materials, both at the Institute and atthe Faculty of Medicine, and bearing in mind the "culture of memory", the work on this text, which is a continuation of the work on the published monograph on the occasion of the 100th anniversary of the establishment of the Institute of Medical Physiology of the Faculty of Medicine of the University of Belgrade and the beginning of classes, was an extremely challenging undertaking. The texts previously published by fellow teachers in faculty publications on the occasion of various anniversaries, as well as in the "Serbian Archive" journal, significantly helped the realization of this undertaking. The willingness and kindness in providing important historiographical material, documents and photographs, by the family members of Professor Richard A. Burian from the USA (Richard M. Burian, Jim Huntington), Milutin Nešković from France and Belgrade (Nenad and Nikola Nešković, respectively) and Božidar Nikolić (Emilija Nikolić Đorić) should be appreciated, and then by numerous colleagues from our country, including Vojislav Voki Kostić, son of the famous professors Aleksandar Đ. Kostić and Smilja Joksić-Kostić. I owe everyone a big thank you, because they made it possible to systematize these important data. However, I am aware that this will not be a complete text, which primarily dealt with the beginnings of work and the restoration of the Institute, and with an exceptional professor and patriot, Prof. Dr. Milutin Nešković, the restorer of the destroyed Institute after the end of the Second World War, whose personality and work, as well as the strength of character, can be a role model for future generations of teachers and associates.  Key words: Faculty of Medicine, Institute of Medical Physiology, Milutin Nešković, Richard Burian, University of Belgrade